1996
DOI: 10.1111/j.1600-0536.1996.tb02162.x
|View full text |Cite
|
Sign up to set email alerts
|

Delayed allergic skin reactions due to subcutaneous heparin‐calcium, enoxaparin‐sodium, pentosan polysulfate and acute skin lesions from systemic sodium‐heparin

Abstract: 2961-3035. 2. Peppercorn M A. Sulfasalazine: pharmacology, clinical use, toxicity and related new drug development. Ann Intern Med 1984: 101: 377-386. 3. Pullar T, Hunter J A, Capell H A. Sulfasalazine in rheumatoid arthritis: a double blind comparison of sulfasalazine with placebo and sodium aurothiomalate. Br Med J 1983: 287: 1102-1104. 4. Das K M, Eastwood M A, McManus J P A, Sircus W. Adverse reactions during salicylazosulfapyridine therapy SHORT COMMUNICATIONS and the relation with drug metabolism and ace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…Until recently, the only therapeutic alternative for our patient would have been an i.v. coumarin derivative, which, while advocated by some authors, has also been found to induce skin reactions (6). The structurally unrelated polypeptide hirudin, produced by recombinant techniques, has now become commercially available (7).…”
Section: Discussionmentioning
confidence: 99%
“…Until recently, the only therapeutic alternative for our patient would have been an i.v. coumarin derivative, which, while advocated by some authors, has also been found to induce skin reactions (6). The structurally unrelated polypeptide hirudin, produced by recombinant techniques, has now become commercially available (7).…”
Section: Discussionmentioning
confidence: 99%
“…The structural similarities of high and low molecular‐weight heparins entail a high likelihood of cross reactions between different kinds of heparin preparations. The heparinoid danaparoid‐Na and the related pentosanpolysulfate have frequently been used as alternatives, yet we and others have reported on skin reaction to the latter as well (1, 2) and a cross‐reactivity between heparins and the former has also been described (3, 4). Hirudin which has been used as alternative drug for patients with heparin induced thrombocytopenia (5) has also been shown to cause delayed‐type hypersensitivity reactions (6, 7) and its repeated application has even led to fatal outcomes.…”
mentioning
confidence: 97%
“…Adverse reactions to various kinds of heparins (high and low molecular‐weight) are a well known problem in daily clinical practice (1). Whereas immediate‐type reactions to heparins are rare, delayed‐type reactions have been increasingly reported in recent years (1). Lesions usually develop 2–4 days after injection and are erythematous, infiltrated and sometimes eczematous in nature.…”
mentioning
confidence: 99%
“…Although no prospective studies have been performed, this complication appears to be extremely rare, since only a limited number of cases of UFH-induced skin necrosis and seven cases (including our case) after LMWH have been reported. In addition, a number of cases of erythematous skin reactions after administration of UFH [9,10,21,23,24] and LMWH [9,10,13,18,21] have been described. In the seven cases of LMWH skin necrosis (Table 1) the lesion developed after about 1 week of treatment, starting with painful erythema and progressing within a short time to necrosis.…”
Section: Discussionmentioning
confidence: 99%